ORIENTATION AND ENTREPRENEURIAL BEHAVIOR OF URBAN AGRICULTURAL ACTORS IN TASIKMALAYA - Riantin Hikmah Widi (INTERNATIONAL JOURNAL OF SOCIAL AND EDUCATION, 2024)
Urban agriculture is an activity that has a dual role and function in urban life, where urban agriculture is not only related to reducing food insecurity which has an impact on public health, urban poverty and improving urban environmental management. Entrepreneurial behavior is very likely to be identified among conventional or semi-commercial farmers. Several entrepreneurial skills are needed for companies that are heavily connected to the market, which requires understanding of the market, human resource management and accurate information management. Entrepreneurial behavior can be seen from another perspective, namely where a farmer takes into account economic risks in their business, is aware of business uncertainty due to climate and market changes, aims to maximize business profits by expanding business activities, is always oriented towards business growth and always pursues opportunities. there for business growth. In general, farmers in Tasikmalaya are semi-commercial farmers, they still run their farming conventionally, are income-oriented, carry out production activities according to the resources they have, and have not adapted to market needs. Farmers collaborate with other mango farmers in the production aspect, but this has not been done in terms of the market.